The Role of Work Motivation as a Mediation of Organizational Culture and Work Environment on Employee Performance at SEMINYAK PARADISO HOTEL - Negara, Made Dwipa; Wibisono, Gunawan; Budiasa, I Ketut (Jurnal Manajemen Pelayanan Hotel, 2024)
This research investigates the mediating role of work motivation in the relationship between organizational culture, work environment, and employee performance at the Seminyak Paradiso Hotel. This research was conducted at the Seminyak Paradiso Hotel which operates in the Hospitality Industry located in the Seminyak area. Using a saturated sample of 55 employees, data was collected through questionnaires, interviews and document analysis. Path analysis shows that organizational culture, work environment, and motivation have a significant and positive effect on employee performance. The findings indicate that Seminyak Paradiso Hotel should prioritize improving the work environment to facilitate optimal task performance and preserve the family-friendly organizational culture.